AL-ADAD WA AL-MADUD DALAM ALQURAN - Jabir, M. (Institut Agama Islam Negeri (IAIN) Palu, 2006)
It is popularly known that Islamic sciences are written in Arabic books (yellow books). From those books, the Muslims learn a variety of Islamic sciences, including Nahw-Sharf (Arabic grammar and structure). Arabic is very important since traditional Islamic sciences such as Qurâan, hadith and earlier ulamaâs thoughts are inherited in Arabic. One of the Qurâanic studies in the light of language is al-Adad (count) wa al-Madud (the things counted). This article tries to explore the two things based on grammatical sciences of Arabic found in the Qurâan.Â Kata Kunci: Al-âAdad, al-Maâdud, Bahasa Arab, Alquran